PENGARUH PENDAPATAN ASLI DAERAH, DANA BAGI HASIL, DANA ALOKASI UMUM, DAN SISA LEBIH PERHITUNGAN ANGGARAN TERHADAP BELANJA BANTUAN SOSIAL PEMERINTAH DAERAH DI ACEH - Teuku Fauzi; Darwanis Darwanis; Syukriy Abdullah (Jurnal Telaah dan Riset Akuntansi, 2014)
ABSTRACT This study aimstoexamine the effect oflocal revenue, sharing fund revenue, general allocation fundandbudgetsurplustosocialaidexpenditureinAceh districs/municipalitie.The research use census methodof heterogeneouspopulationbased on thetarget of criteria that was prescribed within district/municipalitiesinAcehthathavebudget surplus, the value ofgeneral allocation based on the measured of variablethat notminus(after personnel expenditures deducted), andsocial aidexpenditures were spent. The number ofobservationsin this studyof the23district/municipalitiesinAcehof periodfrom 2007 until 2012are136reports of budget spending. Based on specified criteria, there are107reports of budget spending thatmeet thecriteria. The analytical methodusingmultiple linear regression.The results of this study discribes thatlocal revenue, sharing fund revenue, general allocation fundandbudget surplus tosocialaidexpenditureinAceh districs/municipalities, has a constant value is 3.953,292, the value of coefficient X1 is -0,081, the value of coefficient X2 is 0.207, the value of coefficient X3 is -0.018, the value of coefficient X4 is -0.035, with the level of correlation coefficient (R) is 0,396, the coefficient of determination (R2) is 0,157, and the value of Adjusted R2 is 0,124. Keywords    :    Budget, local revenue, sharing fund revenue, general allocation fund,budget surplus, andsocial aid expenditure